2010
DOI: 10.1007/s11764-009-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of androgen deprivation therapy on body composition in men with prostate cancer: Systematic review and meta-analysis

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Abstract Introduction The use of androgen deprivation therapy (ADT) in the treatment of prostate cancer is associated with changes in body composition including increased fat and decreased lean mass.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 58 publications
1
86
1
Order By: Relevance
“…A recent systematic review reported data from eight longitudinal studies (208 total patients) on the effects of ADT on body composition and BMI. 102 The right panel of Figure 3 displays these data as an annualized percent change in BMI in studies with at least 1-year exposure.…”
Section: Bmimentioning
confidence: 99%
See 3 more Smart Citations
“…A recent systematic review reported data from eight longitudinal studies (208 total patients) on the effects of ADT on body composition and BMI. 102 The right panel of Figure 3 displays these data as an annualized percent change in BMI in studies with at least 1-year exposure.…”
Section: Bmimentioning
confidence: 99%
“…The right panel of Figure 5 illustrates the annualized percent change in fat mass reported in four prospective, longitudinal studies with at least 1-year exposure to ADT. These studies, reviewed in a recent meta-analysis, 102 included patients in a wide range of PCa stages with treatment durations of 3-12 months. All studies showed statistically significant increases in fat mass with an average annualized change of 11.1%.…”
Section: Relative Body Fat (% Fat)mentioning
confidence: 99%
See 2 more Smart Citations
“…Testosterone also directly influences changes in body composition by its effects on skeletal muscle. The loss of lean mass and BMD as well as an increase in fat mass following AST are well documented, 6,8,10,51 and although both fat mass and lean mass are both positively associated with bone density because of the effects of gravitational loading on the skeleton, 52,53 the relationship between lean mass and BMD is more powerful owing to the added effect of muscle pull on the skeleton.…”
Section: Osteoporosis and Fractures During And Following Astmentioning
confidence: 99%